Designing an Alternative Typeface to Reflect the Identity of the ITS Campus - Noordyanto, Naufan; Sayatman, (VCD, 2024)
This research aims to design a new typeface that reflects the characteristics of the Institut Teknologi Sepuluh Nopember (ITS) campus and can be used in a variety of contexts. The new typeface, ITS-Artistech, was created by synthesizing key features into the anatomy of Latin letters, which were extracted from the key characteristics and images of the ITS campus. The typeface is intended to be one of several typographic options that reflect ITS and to pioneer typeface production at ITS, contributing to the theoretical and practical body of knowledge on designing typefaces that reflect campus identity. The research method involved collecting data on the use of typefaces in the ITS environment and ITS profile, conducting perceptual studies to know how people perceive the images and characteristics of the ITS campus, and developing the typeface through a series of iterative refinement steps. The new typeface is a valuable resource for the ITS community, as it helps to promote the university's brand, foster a sense of community, and support the creative process and the research of typeface design. It is also a unique and distinctive typeface that is not based on any preexisting letters. The typeface is available as a digital letterform (font) that can be installed and used for a variety of purposes, including digital and print promotional materials.